Wyzysk w upadłości konsumenckiej: brak - Nawacki, Maciej (Studia Prawnoustrojowe, 2019)
The article is concerned with the analysis of the new regulation of consumer bankruptcy. The author draws attention to the relationship between bankruptcy proceedings and the exploitation of insolvent consumers. The legal analysis indicates that the new regulation of consumer bankruptcy allows effective improvement in the situation of insolvent consumers. The article is summarised with theoretical consideration of useful methods of debt cancellation